Development of Game Based basic Speed Running Movement Training for Children Age 7 - 9 Years - Taufik Rahmadi; Moch. Asmawi; Hidayat Humaid (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
The aim of this research is to develop basic sprint movement training for 7-9 year olds, and to determine the effectiveness of the model developed. The method in this research is the Research & Development model approach from Borg and Gall. The aim of this research is to develop a game-based basic movement training model for sprinting for ages 7-9 years. The small group trial consisted of 20 people, while the large group trial consisted of 30 people. Data collection in this research is by reviewing various literature or literature studies related to the model concept that will be developed according to the product to be made and referring to the needs of analysis, expert reviews and field trials. To calculate effectiveness, the t-test procedure is used. The research results of the game-based basic movement training model for sprinting are appropriate to the characteristics of children aged 7-9 years and are effective for improving sprinting.